Studi Literatur : Penerapan QRIS Sebagai Payment Gateway dalam Mendukung Efisiensi Sistem Informasi Akuntansi pada UMKM - Ayu Intan Febriana; Aris Eddy Sarwono; Fadjar Harimurti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is a literature review that examines the role of QRIS as a payment gateway in improving the efficiency of Accounting Information Systems (AIS) in MSMEs. Digital transformation in payment systems is key to speeding up, enhancing accuracy, and securing transaction records. QRIS provides a practical solution by integrating various non-cash payment methods into one system, enabling automated real-time recording and faster financial reporting. A review of ten studies shows QRIS helps speed up recording, ease reconciliation, reduce input errors, and serve as a strategic tool for AIS digitalization in the digital economy era.